The Role of Job Adjustment in Job burnout with Supervisor Support as a Mediating Variable in the Relationship: Case study of Alpha Pipe Company in the state of Ghardaia - Hiba, Abdelfattah; Chergui, Mehdi (Dirassat Journal Economic Issue, 2023)
This study aimed to verify the impact of job Adjustment on job burnout with supervisor support as a mediating variable on workers in Alpha Pipe Company for Pipes in the state of Ghardaia, The descriptive approach was used, which is concerned with data collection and analysis in this light, and this is by relying on previous studies for the theoretical aspect, and the questionnaire designed from several previous studies to show the views of the (131) workers as a final sample whose answers were analyzed by several means The calculations provided by (Spss v28) and (Amos v26), The results of the study concluded that the supervisor’s support mediated the relationship between job Adjustment and job burnout, but the direct effect of the supervisor’s support on job burnout alone had a negative effect